A eficiência do gasto e da qualidade da saúde pública: uma análise nos municípios do estado do Rio Grande do Norte (2004 e 2008) - Queiroz, Maria de Fatima Medeiros de (2012)
The overall objective of this study is to analyze the efficiency in the use of resources and the quality of public health in the municipalities of Rio Grande do Norte, from 2004 to 2008. It also seeks to identify the determinants of municipal inefficiency and measure the productivity of public spending on health. To this end, three methods of analysis are used: the DEA, the Malmquist index and the Tobit regression model. Among other findings, it appears that municipalities considered more inefficient in the measurement of expenditure on health make the largest expense in this function. On the other hand, from 2004 to 2008, only 13 municipalities showed an increase in the productivity of public spending. It is also noted that municipalities considered efficient in quality of health, although having more physical and human resources, offer fewer health services to the population. In all, the major determinants of health spending inefficiencies are the variables: age of the mayor, coalition, population density, literacy race and budget revenues. Regarding the inefficiency of the health quality, variables such as: coalition, literacy race have strong influence on this behavior. Thereby, the hypotheses proposed by the study have been fully accepted. In other words, for the efficiency of the quality and health spending it is needed more than resources, i.e., the expenditure shows itself as essential, but not enough, for political and economic aspects also interfere with the performance of spent and in the quality of health care offered to the population